Pengaruh Konten Vloggers Youtube Jess No Limit terhadap Pembentukan Sikap Gen Z - Achmad Fachri Wahyudi; Gita Widiasanty; Nur’aeni Nur’aeni (Institut Nalanda, 2024)
Technological advances have created new forms of interaction and socialization, one of which is the innovation of communication technology in the form of social media. One of the social media that is very popular among the younger generation is YouTube. YouTube content has a variety of content according to needs, such as game content, entertainment content, beauty content and many more. The rapid development of social media, one of which is YouTube, Indonesia itself has several famous Vloggers, one of which is Jess No Limit. Tobias Justin or now better known as Jess No Limit started his career as a Youtuber in 2020 with the content of the Mobile Legend Esport Game: Bang Bang and for the first time in Indonesia Jess No Limit managed to have 10 million subscribers, YouTube content itself has had an impact on attitudes. The purpose of this study is to determine and analyze whether or not there is an influence of Youtube vloggers Jess No Limit's content on the formation of Gen Z attitudes. The theory used in this study is content and attitude. The method used in this study is quantitative with descriptive analysis, to analyze data by describing or depicting the data that has been collected. Statistical analysis and data processing using SPSS. Data collection includes questionnaires, online questionnaires, data analysis, data interpretation, and conclusions. Primary data in the form of a questionnaire on a Likert scale model with the number of respondents using the Slovin sample formula being 66 respondents. The results of the study showed that there was a positive and significant influence between the influence of Jess No Limit YouTube content on the formation of attitudes with a moderate level of influence.